Thinking styles and professional choice in three Mexican universities - Valadez Huizar, Martha (2017)
It has been proved that differences in Thinking Styles (TS) exist between students along distinct professional fields, and this supports that TS are socialized by different scholar professional environments. Nonetheless there is a lack of studies directed to answer if professional choice is influenced by TS. Two purposes guided the present work: describe the relationship between TS and professional choice and search for differences in TS between students of public and private universities, with the aim of gathering psychoeducational data of cognitive characteristics from students since their very first contact with university environment. In this quantitative, descriptive study 2 877 first-year college students of one public and two private universities answered the 104 items Thinking Styles Questionnaire designed by Sternberg. Participants were grouped into five thematic areas: Administration (n=967), Architecture/Design (n=449), Engineering (n=454), Health (n=272) and Social Sciences (n=574). Results showed a general EP profile of college students, as well as differences between public and private universities and between thematic areas, supporting socialization of TS and suggesting future research on development of cognitive changes associated with a “culture of a professional TS” from beginning to ending of professional careers.